The association between empirical dietary inflammatory pattern and risk of cancer and cancer-specific mortality: a systematic review and meta-analysis of prospective cohort studies - Hosseini, Fatemeh S.; Nikparast, Ali; Etesami, Elahe; Javaheri-Tafti, Fatemeh; Asghari, Golaleh (Frontiers in Nutrition, 2024)
Background/aim Current evidence indicates a correlation between the inflammatory potential of diet and the risk of cancer and cancer-specific mortality. This study aimed to assess the association between empirical dietary inflammatory pattern (EDIP), which has recently been designed based on the inflammatory potential of the diet, and the risk of cancer and cancer-specific mortality. Methods A systematic literature search was conducted across the PubMed/Medline, Scopus, and Web of Science databases from January 2016 to March 2024. A random effects model was used to calculate the pooled effect size (ES) and 95% confidence intervals (95% CI). Heterogeneity between studies was assessed using the Cochran Q test and the I2 statistic. Results From the initial 229 records, 24 prospective cohort studies with 2,683,350 participants and 37,091 cancer incidence cases, as well as 20,819 cancer-specific mortality, were included in our study. Pooled results indicated a significant association between higher adherence to the EDIP and an increased risk of total cancer (ES: 1.10; 95% CI: 1.05–1.15; I2 = 41.1), colorectal cancer (ES: 1.19; 95% CI: 1.11–1.27; I2 = 41.1), and liver cancer (ES: 1.48; 95% CI: 1.14–1.94; I2 = 36.9). However, no significant association between increased adherence to the EDIP and an increased risk of ovarian or endometrial cancer was found. Furthermore, greater adherence to the EDIP was significantly associated with an increased risk of cancer-specific mortality (ES: 1.18; 95% CI: 1.05–1.33; I2 = 45.4). Conclusion Our results showed that a diet with higher inflammatory properties is associated with an increased risk of cancer and cancer-specific mortality. Systematic review registration PROSPERO registration no. CRD42024496912.